The beginnings of electron microscopy - Hawkes, P. W. (Advances in electronics and electron physics. Supplement, 1985)
The Beginnings of Electron Microscopy presents the technical development of electron microscope. This book examines the mechanical as well as the technical problems arising from the physical properties of the electron. Organized into 19 chapters, this book begins with an overview of the history of scanning electron microscopy and electron beam microanalysis. This text then explains the applications and capabilities of electron microscopes during the war. Other chapters consider the classical techniques of light microscopy. This book presents as well the schematic outline of the preparation.